Notebook : Issue 6 : In the Moment of Match-Strike (New York : MUBI Inc., 2024)
Issue 6 is dedicated to different expressions of youth in cinema, a time of surprise, invention, rebellion, and hope for the future. In a cross-generational feature, a group of parents curate a short film program and share the reactions (and drawings) of their own children. Plunging bravely into the madcap “microcinematic” world of videos found across TikTok, YouTube, and Instagram feeds, filmmaker Nikita Lavretski provides a critical guide to one day’s intense viewing; in another artist contribution, Fox Maxy handwrites an inspiring letter to her younger self. Other features include academic Christopher Holliday on digital de-aging, visual artist Jonas Staal on product placement’s childhood targets, critic Philippa Snow on teenage fascination with visual extremity, and writer Adam Wray on bootleg movie merchandise. In a roundtable feature, the makers and voices of the animated series Daria tell Claire Marie Healy how they channeled teenage disaffection, and participants and teachers share photographs and memories from New York’s impactful Young Filmaker’s Foundation. Writer and director Durga Chew-Bose pinpoints cinematic moments that evoke a timeless childhood, and a selection of poems by avant-gardist Shūji Terayama, written when he was a young adult in mid-century Japan, further attest to the enduring fire of youth. Elsewhere in the magazine, Amalia Ulman and Payal Kapadia continue our multi-issue series “Things a Filmmaker Should Know,” the revelation of rare and restored imagery marks the centennial of Sergei Parajanov’s birth, and an unsung but brilliant special effects pioneer is given his due.
Notebook is a publication dedicated to cinema art and culture, created as an extension of indie cinema streaming platform, MUBI. This shiny fourth issue arrives just in time for the holiday season and is subtitled 'Film is definitely not a "visual medium"', in reference to an essay by sound designer Randy Thom. Inside, the team take a look at—or rather, lend an ear to—the sonic side of film, featuring melodic visualisations, the history of the phonoscène (aka 'a very early precursor to the music video') and the art of narrating and improvising, and a trip to The Foley Lab in County Wicklow, Ireland, where they shot a series of homemade sound props—watermelons for pulling out hearts, hot water bottles for screeching tires and more.
boek